PENGEMBANGAN LKS TEMATIK BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) SUB TEMA ANGGOTA KELUARGAKU UNTUK SISWA KELAS 1 SEKOLAH DASAR - ZAENOL FAJRI (KEGURU "Jurnal Ilmu Pendidikan Dasar", 2020)
To improve the quality of education must use good teaching materials, one teaching material that can be used is a thematic student worksheet that can improve the learning process because it is following the level of development of elementary school students. The thematic worksheets that are developed are connected directly to real life in the environment around students, so the learning process will become more meaningful. The purpose of this study was to produce a thematic student worksheet based on contextual teaching and learning of my family members' sub-themes developed according to the elements of validity, effectiveness, practicality, and attractiveness. This study uses a 4-D development model developed by Tiagarajan and Sammel (1974), namely (1) Define, (2) Design, (3) Develop and (4) Disseminate. The results of this study, the average validity reached 84.2% (very valid). The effectiveness is 84.3% (very effective), the practicality of the product reaches 87.2% (very good) and the attractiveness of the product reaches 86.0% (very attractive). The conclusion of the results of this study, Thematic Worksheet Based Contextual Teaching and Learning can be used by teachers and students as one of the practical, effective and efficient teaching materials.